Consumo de antibacterianos en un establecimiento farmacéutico privado de Trujillo, 2017 - Narro Zavaleta, Elvis Alexander (2019)
This report of pre-professional practices aims to determine the characteristics of the consumption of antibacterials expended in a private pharmaceutical establishment of Trujillo expressed in defined daily dose (DDD) per 1000 attentions per day, during 2017, in order to contribute to the rational use and efficient of these medications. Outpatient antibacterial units and some hospital use units dispensed in a private pharmaceutical establishment with an average of 480 clients per day were considered. The data were obtained from the internal computerized computer system of the pharmaceutical establishment, also the consumption was expressed in terms of defined daily dose (DDD) per 1000 attentions per day. The results obtained for the antibacterials were, azithromycin with 2,554 DDD / 1000 attention / day, dicloxacillin with 0,343 DDD / attention / day, amoxicillin with 1,843 DDD / 1000 attention / day, ciprofloxacin 1,0242 DDD / 1000 attention / day, levofloxacin with 0,259 DDD / attentions / day, cephalexin with a 0,125 DDD / 1000 attentions / day, cefadroxil with 0,112 DDD / attentions / day, clarithromycin with 0,324 DDD / attentions / day, erythromycin with 0,036 DDD / 1000 attentions / day and sulfamethoxazole + trimetropim with 0,473 DDD / attention / day. The total cost of the antibacterials consumed was S/ 62463,3 with azithromycin being the highest cost with S/ 20211,94 which represents 32%.